PENERAPAN CUCI TANGAN PESERTA DIDIK DI RUMAH SAKIT GIGI DAN MULUT UNIVERSITAS GADJAH MADA PROF. SOEDOMO - Fitrina Rachmadanty Siregar; Andreasta Meliala (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2020)
Background: Dental health professionals have potential infection risks during treatment for the patients. Performing good hand hygiene is very important to prevent the transmission of infections including in dental practice. However, various studies have shown that health workers have low compliance to hand hygiene. Some factors influence the compliance of health workers in hand hygiene practice are knowledge, perceptions, attitudes, workload, and the availability of hand hygiene facilities. Objective: The aim of the study was to improve the compliance of the dental clerkship students’ hand hygiene practice at UGM Prof. Soedomo Dental Hospital. Methods: The research design was action research. Quantitative data was collected during the diagnosing action through a questionnaire on knowledge and perceptions of hand hygiene and observation of hand hygiene compliance among 35 students, focus group discussion (FGD) on four students, and evaluating the hand hygiene facilities for students. The data collected in initial stage was used to determine the planning action, taking action, and evaluation stage. Results: The hand hygiene compliance of the students increased by 60% after dissemination of hand hygiene standard procedures, hand hygiene training, improving hand hygiene facilities, and increasing the commitment using consent forms before treating patients. The result of the Wilcoxon Signed Rank Test showed a Z value of -4.583 with a p-value of 0.000 (p<0.05). Conclusion: It can be concluded that the hand hygiene compliance of clerical students in UGM Prof. Soedomo Dental Hospital increase significantly by the policy and management interventions.